2014
DOI: 10.1109/mic.2014.19
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing Implicit Social Networks in Multiplayer Online Games

Abstract: Abstract-For many networked games, such as the Defense of the Ancients and StarCraft series, the unofficial leagues created by players themselves greatly enhance user-experience, and extend the success of each game. Understanding the social structure that players of these games implicitly form helps to create innovative gaming services to the benefit of both players and game operators. But how to extract and analyse the implicit social structure? We address this question by first proposing a formalism consisti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(35 citation statements)
references
References 4 publications
2
33
0
Order By: Relevance
“…One direction is to use the social structure of the players in online games to help with the prediction. It has been shown that the players are more likely to play games with their "friends" [47]. This may help to predict the ending times more accurately by considering closely related players together.…”
Section: Discussionmentioning
confidence: 99%
“…One direction is to use the social structure of the players in online games to help with the prediction. It has been shown that the players are more likely to play games with their "friends" [47]. This may help to predict the ending times more accurately by considering closely related players together.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, authors have found application in social network analysis of online multi-player games to identify and investigate social communities, to identify cheaters, or recommend match partners [6,7,22,31,38,39] and to investigate the impact of social aspects on in-game behavior, game performance, engagement, and retention [33] in games and multi-user environments such as Ωorld of Ωar-craft, Second Life, or Destiny. Especially correlations between social network metrics and behavioral features or performance measures have been shown as valuable tools to utilize social network analysis [12,29,33].…”
Section: Social Network Analysis (Sna)mentioning
confidence: 99%
“…There are various ways of defining or determining affinity in an MMVE, and with the research focus in the domain shifting towards socio-technical systems and their characteristics, more indicators are identified, for instance, based on the history and nature of previous interactions [3]. Picking a set of inclination factors, the fundamental idea behind the proposed connection scheme is to consider the notion of structural balance from the beginning and constructively reflect the process, maintaining inter-faction links only where necessary to ensure a certain degree of connectedness.…”
Section: Including Structural Balancementioning
confidence: 99%